EVALUATION OF DRAINAGE SYSTEM IN SRIKOYO STREET PATRANG DISTRICT, JEMBER REGENCY: Kajian Evaluasi Sistem Drainase Jalan Srikoyo Kecamatan Patrang Kabupaten Jember - Tamimi, Rusyidina; Wahyuni, Sri; Hidayah, Entin (Jurnal Rekayasa Sipil dan Lingkungan, 2017)
The water logging or even flood always occurs on Srikoyo road in every rainy season. The condition emerges because of the imbalance between the number of rainwater catchment area and the rapid increase of residential areas. Besides, the drainage channels along the road of Srikoyo are not sufficient enough to hold rainwater well. The process of evaluation is done by applying the method of hydrological analysis to determine the maximum discharge modeling used for evaluating the capacity of the existing drainage channels. The output of the hydrology analysis calculation comes up in rainfall intensity which is required as the data input for SWMM modeling. SWMM modeling is used in this evaluation since it is a model of rainfall-runoff simulation which is used for simulating both quantity and quality of the surface runoff of urban areas. The result of the evaluation using the software SWMM suggests that there are several number of water logging during the return period of 1, 2, 5, and 10 years. There are 3 areas encounter flood in the return period of 1 year, 10 areas in the return period of 2 years, 18 areas in the return period of 5 years, and 19 areas in the return period of 10 years. Pada musim penghujan Jalan Srikoyo selalu tergenangi air. Terjadinya genangan di Jalan Srikoyo diakibatkan oleh area resapan air hujan tidak seimbang dengan pesatnya wilayah pemukiman. Selain itu, saluran drainase di sepanjang ruas Jalan Srikoyo kurang memadai dan tidak dapat berfungsi dengan baik untuk menampung air hujan. Dengan adanya permasalahan ini dilakukan proses evaluasi, evaluasi ini dilakukan dengan menggunakan metode analisis hidrologi untuk menentukan debit pemodelan maksimal yang digunakan untuk mengevaluasi kapasitas saluran drainase yang ada. Dimana output perhitungan analisis hidrologi berupa intensitas hujan yang diperlukan sebagai data inputan untuk pemodelan SWMM. SWMM digunakan dalam evaluasi ini dikarenakan SWMM merupakan model simulasi hujan-aliran (rainfall-runoff) yang digunakan untuk mensimulasikan kuantitas maupun kualitas limpasan permukaan dari daerah perkotaan. Dari evaluasi menggunakan software SWMM, pada kala ulang 1 tahun didapatkan 3 node lokasi banjir, kala ulang 2 tahun didapatkan 10 node lokasi banjir, kala ulang 5 tahun didapatkan 18 node lokasi banjir dan kala ulang 10 tahun didapatkan 19 node lokasi banjir.